Assessing the Carbon Benefits of Improved Land Management Technologies - Braimoh, Ademola (World Bank, Washington, DC, 2012)
Ensuring food security under changing climate conditions is one of the major challenges of our era. Agriculture must not only become increasingly productive, but must also adapt to climate change while reducing greenhouse gas emissions. Soil carbon sequestration, the process by which atmospheric carbon dioxide is taken up by plants through photosynthesis and stored as carbon in biomass and soils, can support these goals. First, soil carbon enhances agricultural productivity, which reduces rural poverty; second, it limits greenhouse gas concentrations in the atmosphere; and third, it reduces the impact of climate change on agricultural ecosystems. This smart lesson describes the potential benefits of selected land management technologies that sequester carbon.